Pengembangan Pembelajaran Pendidikan Kesehatan Melalui Personal Health Card Assignments Untuk Peserta Didik Sekolah Menengah Atas (Universitas Negeri Semarang, 2021)
The purpose of this research is to produce teaching material products as a guide that can optimize the health education learning materials through personal health card assignments. The research method in this study is qualitative. Sample in this study were students at Pegandon High School, 1st Kendal High School and 2nd Kendal High School. The results of the study obtained an evaluation of health education experts with an average percentage of 71% in the